Síntese de uma série de tiossemicarbazonas derivadas do (-)-Canfeno e avaliação da atividade frente à Mycobacterium tuberculosis - Souza, Mariana Regina Passos de (2016)
Over time Organic Synthesis discovery of new drugs with biological activity, often using natural products such as synthetic precursors for obtaining the compounds with diverse pharmacological potential. Among natural products that excel in this scenario are the monoterpenes, which have different synthetic compounds, and pharmacological applications. Synthetic point of view, these molecules may be important chiral substrates to obtain new drugs, in addition to a large part to have high availability and low cost possess some representatives. On the other hand, thiosemicarbazones are of considerable scientific interest because of their easy synthetic acquisition and the significant pharmacological activity. However, it is very common the presence of substitution by alkyl or aryl groups in imínica position N-1, are rare cases where the replacement occurs at the N-4 position. This work aimed to thiosemicarbazide training as a synthetic reaction intermediate for obtaining thiosemicarbazone substituted N-4 by monoterpene unit (-) - camphene. This was obtained by condensation with hydrazine isotiocianomonoterpeno resulting in the desired substitution at C-4 position. 21 thiosemicarbazone derived were synthesized (-) - camphene varying the substituent groups on imínica position C-1 with the use of various carbonyl derivatives benzaldehyde and derivatives p-OMe, p-Me, p N (Me) 2, -OH, p-OH, pC (CH3) 3 pF, f, o-Cl, mf, p-CF3, p-Br, p-NO2, p-Cl; heterocícilos aldehydes: 2-nitro-5-tiofenocarboxialdeído and 2-nitro-5-furaldehyde and isatin. The derivatives were obtained in good yields and characterized by various spectroscopic techniques. After characterization, the synthesized molecules were evaluated for their potential anti-tuberculosis activity. It was found that when inserting new nitrogenous groups to the (-) - camphene was an increase in activity for the derivatives. Of the 22 compounds obtained, 10 showed relatively good results in in vitro tests as well as being found that the heterocyclic radicals are more activity against Mycobacterium tuberculosis bacteria.